Protective Effect of Oyster Peptides Derived From Crassostrea gigas on Intestinal Oxidative Damage Induced by Cyclophosphamide in Mice Mediated Through Nrf2-Keap1 Signaling Pathway - Chen, Hui; Zheng, Huizhen; Li, Tiejun; Jiang, Qihong; Liu, Shulai; Zhou, Xuxia; Ding, Yuting; Xiang, Xingwei (Frontiers in Nutrition, 2022)
Oyster peptide (OP) has exhibited useful biological activities and can be used in multi-functional foods. OP has been reported to play a significant role in intestinal protection, but its specific mechanism is still not completely understood. The aim of this study was to analyze the potential effect of OP on oxidative damage of mice intestine induced by cyclophosphamide (Cy). The experimental results revealed that intragastric administration of OP significantly increased average bodyweight, improved ileum tissue morphology and villus structure, as well as increased the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) in oxidized mice serum and liver. The content of malondialdehyde (MDA) in the mice serum and liver homogenate was found to be markedly decreased. Moreover, OP significantly increased the relative mRNA expression levels of superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), quinone oxidoreductase (NQO1) and heme oxidase-1 (HO-1) in ileum. Western-blot results indicated that prior administration of OP significantly up-regulated the Nrf2 production in ileum, and substantially decreased then Keap1 gene expression. In conclusion, intake of OP was found to markedly improve intestinal oxidative stress in vivo, and this effect was primarily mediated through the simulation of antioxidant Nrf2-Keap1 signaling pathway.